Identifying suboxide grains at the metal–oxide interface of a corroded Zr–1.0%Nb alloy using (S)TEM, transmission-EBSD and EELS - Hu, J; Garner, A; Ni, N; Gholinia, A; Nicholls, R; Lozano-Perez, S; Frankel, P; Preuss, M; Grovenor, C (Elsevier, 2014)
Here we report a methodology combining TEM, STEM, Transmission-EBSD and EELS to analyse the structural and chemical properties of the metal–oxide interface of corroded Zr alloys in unprecedented detail. TEM, STEM and diffraction results revealed the complexity of the distribution of suboxide grains at the metal–oxide interface. EELS provided accurate quantitative analysis of the oxygen concentration across the interface, identifying the existence of local regions of stoichiometric ZrO and Zr3O2 with varying thickness. Transmission-EBSD confirmed that the suboxide grains can be indexed with the hexagonal ZrO structure predicted with ab initio by Nicholls et al. (2014). The t-EBSD analysis has also allowed for the mapping of a relatively large region of the metal–oxide interface, revealing the location and size distribution of the suboxide grains.